A new technique based on Ant Colony Optimization for designing mining pushbacks in the presence of geological uncertainty (Rudarsko-geološko-naftni zbornik, 2023)
An essential task in the open-pit mine optimizing process is determining the extraction time of material located in the ultimate pit, considering some operational and economic constraints. The proper design of pushbacks has a significant impact on the optimum production planning. On the other hand, some uncertainty sources such as in-situ grade cause both deviations from production and financial goals. This paper presents an extension of a multi-stage formulation for risk-based pushback designing that utilizes the ant colony optimization (ACO) algorithm to solve it. For more detailed studies, two different strategies were developed according to statistical and probabilistic issues. The data of Songun copper mine located in NW Iran was used to evaluate the ability of the proposed approach in controlling the risk of deviation from production targets and increasing the project value. The results indicated the effectiveness of the proposed approach in pushback designing based on geological uncertainty. Examining different strategies showed that the technique based on multiple probability produces better solutions.